App Design Method Based on A-KANO and SOC-TM Models: A Case Study of a Healthy Diet App for the Elderly - Wei Liu; Xing-Yuan Li; Wei-Jie Liu; Yi-Nan Fei (IEEE Access)
This study addresses the research gap in designing health diet apps for elderly individuals with chronic diseases, as most existing apps target younger users and fail to meet the specific needs of older adults. Utilizing the A-KANO model for design optimization and the SOC-TM model for usability evaluation, we developed a “Diet and Medicine Health” app tailored for elderly users. The findings indicate that design improvements based on the A-KANO model significantly enhance operational efficiency, task execution effectiveness, and user satisfaction. The app outperforms the “Mint Health” app in terms of efficiency and usability, particularly in reducing cognitive load and operational errors. However, this study has limitations, including a relatively small sample size and a focus on a specific demographic. Future research should expand the sample range and explore the integration of emerging technologies to further enhance app functionality. This research provides valuable theoretical insights and practical guidance for designing age-friendly health apps.